PENGARUH KONSUMSI KEJU CHEDDAR 10 GRAM TERHADAP pH SALIVA - Studi terhadap Mahasiswa Fakultas Kedokteran Gigi Universitas Islam Sultan Agung Semarang - Nadia Fitri Hapsari; Ade Ismail; Oedijono Santoso (Odonto : Dental Journal, 2014)
Background: Dental caries is the main problem of oral health in the world. The preventive is consumption cheddar cheese with caseinfosfoprotein and calcium. This study aimed to determine whether the consumption of 10 grams cheddar cheese can increase salivary pH. Method: The type of this research method is experimental with pre and post design. The samples in this research were 30 students FKG Unissula who inclusion criteria, 10 people the treatment group (consuming 10 grams of cheddar cheese), 10 people positive control group (consuming chocolate biscuits), and 10 people negative control group. The data analysis techniques using Paired T Test to determine the salivary pH before and after treatment. Furthermore, to know differences among the three groups using One Way Anova Test and Post Hoc Test . Result: Based Test Paired T Test showed that the treatment and negative group increased salivary pH. Positive control group decreased salivary pH. Based on One Way Anova test significant value 0.000 (p≤0.05), it means differences between 3 groups. Based on Post Hoc Test found significant value p≤0.05, it means differences between one group to another. Conclusion: From study result concluded that consumption 10 grams of cheddar cheese can raise the salivary pH.